Beyond the Black Queen Hypothesis - Mas, Alix (ISME J, 2016)
The Black Queen Hypothesis, recently proposed to explain an evolution of dependency based on gene loss, is gaining ground. This paper focuses on how the evolution of dependency transforms interactions and the community. Using agent-based modeling we suggest that species specializing in the consumption of a common good escape competition and therefore favor coexistence. This evolutionary trajectory could open the way for novel long-lasting interactions and a need to revisit the classically accepted assembly rules. Such evolutionary events also reshape the structure and dynamics of communities, depending on the spatial heterogeneity of the common good production. Let Black be the new black!